The Impact of Foreign Aid on Economic Development and the Role of the Institutional Quality - Tokar, Berkan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
This study, will attempt to empirically analyse the achievements or failures of foreign aid on economic growth from different perspectives, such as the role of institutional quality, investment volatility and foreign agricultural aid on food security, in the different economies of Sub-Saharan Africa over a given period of time. In the second chapter of this study, the interconnectivity of growth, aid and institutions in Sub-Saharan Africa were analysed, based on annual data for a panel of 39 nations from 1996 to 2017. The hypothesis that the growth impact of aid and institutions could be interactive was examined. The hypothesis was tested using panel data series for official development assistance, aggregate and individual measures of institutional quality and economic growth, while controlling for sub-regional differences in Southern Africa, Eastern Africa, Western Africa and Central Africa. The results indicate that aid has a direct positive and an indirect negative growth impact through its interaction with domestic institutions. The synergistic growth impact of aid and institutions is found to be substitutive rather than complementary. Good quality institutions are positively correlated with growth, and the institutions that reduce rent seeking and protect property rights are the types of institutions with the biggest growth effects. In addition, Foreign agricultural aid has been put forward as a viable complement to domestic resource mobilization in filling the resource gap. The third chapter thus empirically examines the impact of foreign agricultural aid on food security in Sub Saharan Africa over the period 2002-2017. Based on the methodology stated in this chapter, the following conclusions have been reached: (i) Foreign aid to agriculture can indeed help to fill the resource gap (ii) The nature of causal relations between per capita calorie intake and foreign agricultural aid shows that foreign agricultural aid is an important predictor of food security. (iii) Foreign agricultural aid directed towards increasing agricultural productivity helps to cope with a rising population. (iv) Feedback suggests the existence of a vicious cycle in which SSA countries with weaker institutions receive more agricultural aid which further weakens the quality of institutions in these countries. Finally, in the fourth chapter of this study, it is known that sustained investment is required for economic growth. Investment, however, often experiences severe volatility in poor countries, making spending plans difficult to formulate and diminishing growth potentials. Foreign aid serves as an important source of complementary financing for sustained investment. This paper therefore studies the effect of aid inflows on total investment volatility in 19 heavily-indebted, poor Sub Saharan African countries over the period 1980 to 2017. Employing the cross sectionally augmented distributed lag (CS-DL) estimation technique for long-run coefficients in dynamic heterogeneous panels with cross-sectional dependence, along with bootstrap panel causality testing, we show that aid has an inverse relationship with volatility. The fourth chapter thus conclude that aid can be viewed as a dampening factor for investment volatility in poor countries. Keywords: Economic Growth, Official Development Assistance, Institutions, Sub Saharan Africa, Panel GMM, Food security, Foreign aid, Investment volatility, Cross sectional dependence, Slope heterogeneity, CS-DL, Bootstrap panel Granger causality

ÖZ: Bu çalışmada, dış yardım uygulamalarının ekonomik büyüme üzerindeki başarısında veya başarısızlığında, kurumsal kalitenin rolü, yatırım dalgalanmaları ve ayrıca gıda güvenliğindeki dış kaynaklı tarımsal yardım gibi farklı perspektiflerde ele alarak, farklı ekonomilerde değerlendirildi. Deneysel olarak belirli bir zaman diliminde Sahra Altı Afrika ülkeleri örneklenerek analiz çerçevesi oluşturuldu. Dolayısıyla bu çalışmanın ilk bölümünde, Sahra Altı Afrika Ülkeleri’ndeki büyüme, yardım ve kurumların birbirleri ile etkileşimi, 1996'dan 2017'ye kadar 39 ülkeden oluşan bir panel çerçevesinde yıllık verilere dayanılarak analiz edildi. Dış yardımlar ve kurumların büyüme üstünde etkisinin olabileceği hipotezi interaktif olarak incelendi. Hipotez, Güney Afrika, Doğu Afrika, Batı Afrika ve Orta Afrika'daki bölgesel farklılıklar kontrol edilirken, resmi kalkınma yardımı, kurumsal kalitenin toplu ve spesifik ölçümleri ve ekonomik büyüme için panel veri serileri kullanılarak test edildi. Sonuçlar, yardımın yerel kurumlarla etkileşimi yoluyla doğrudan olumlu ve dolaylı olarak olumsuz bir büyüme etkisine sahip olduğunu göstermektedir. Dış yardım ve kurumların sinerjik büyüme etkisinin tamamlayıcı olmaktan çok ikame edici olduğu bulunmuştur. Kaliteli kurumlar ekonomik büyüme ile pozitif yönde ilişkilidir ve rant arayışını azaltan ve mülkiyet haklarını koruyan kurumlar, büyüme etkilerinin en büyük olduğu kurum türleridir. Öte yandan yabancı tarımsal yardım, kaynak açığının doldurulmasında yerel kaynak seferberliğinin uygulanabilir bir tamamlayıcısı olarak öne sürülmüştür. Bu bölüm, böylelikle 2002-2017 döneminde Sahra Altı Afrika'da yabancı tarımsal yardımın gıda güvenliği üzerindeki etkisini ampirik olarak incelemektedir. Çalışma metodolojisine dayanarak aşağıdaki sonuçlara ulaşılmıştır; (i) Tarıma yönelik dış yardım, gerçekten de GGD ülkelerinin kaynak açığını kapatmaya ve uzun vadede kişi başına kalori alımını önemli ölçüde artırmaya yardımcı olabilir. (ii) Kişi başına kalori alımı ile yabancı tarımsal yardım arasındaki nedensel ilişki, yabancı tarımsal yardımın gıda güvenliğinin önemli bir göstergesi olduğunu göstermektedir. (iii) Nüfus büyüklüğü, SSA'da gıda güvenliği üzerinde en büyük etkiye sahiptir. Bu nedenle, artan nüfusla başa çıkmak için tarımsal üretkenliği artırmaya yönelik yabancı tarımsal yardım, gıda güvensizliği sorununun çözülmesi için hayati önem taşımaktadır. (iv) Yabancı tarımsal yardım ile kurumsal kalite arasında nedensel ilişki, daha zayıf kurumlara sahip ülkelerin daha fazla tarımsal yardım aldığı ve bu ülkelerdeki kurumların kalitesini daha da zayıflatan bir kısır döngünün varlığını göstermektedir. Son olarak, bu çalışmanın son bölümünde, ekonomik büyüme için yatırım devamlılığı gereklidir. Ancak yatırımlar, genellikle gelir seviyesi düşük ülkelerde harcama planlarının formüle edilmesini zorlaştırır ve ekonomik büyüme potansiyellerini azaltır. Bu makale, 1980-2017 döneminde, 19 ağır borçlu, yoksul Sahra Altı Afrika ülkesinde yardım girişlerinin toplam yatırım dalgalanmaları üzerindeki etkisini incelemektedir. Bu çalışmada kullanılan çeşitli ölçüm teknikleri ve gerekli testlerin ardından dış yardımların, dalgalanma ile ters bir ilişkisi olduğunu görülmektedir. Böylelikle yardımın Yoksul ülkelerdeki yatırım oynaklığını azaltıcı bir faktör olarak görülebileceği sonucuna varılmaktadır. Anahtar Kelimeler: Ekonomik Büyüme, Resmi Kalkınma Yardımları, Kurumlar, Sahra Altı Afrika, Gıda Güvenliği, Dış Yardım, Yatırım Volatilitesi, Yatay Kesit Bağımlılığı, Eğim Heterojenliği, İçsel Panel Granger Nedensellik
Doctor of Philosophy in Economics. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2021. Co-Supervisor: Assoc. Prof. Dr. Kamil Sertoğlu and Supervisor: Prof. Dr. Mehmet Balcılar.
Keywords: Economics; Foreign Aid-Economic Development-Africa; Economic Growth; Official Development Assistance; Institutions; Sub-Saharan Africa; Panel GMM; Food security; Foreign aid; Investment volatility; Cross-sectional dependence; Slope heterogeneity; CS-DL; Bootstrap panel Granger causality